2011
DOI: 10.1007/s10493-011-9432-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative population dynamics of a generalist (Ixodes ricinus) and specialist tick (I. hexagonus) species from European hedgehogs

Abstract: Although the population dynamics of the tick Ixodes ricinus are relatively well studied, those of other Western European tick species are largely unknown. Moreover, there is very little information related to the interactions between I. ricinus and other ticks. Such knowledge, however, is of special interest in respect to the epidemiology of tick-borne pathogens such as Borrelia spp. We compared the dynamics of the generalist I. ricinus with the nest-dwelling hedgehog specialist, I. hexagonus. Both species wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 45 publications
2
41
1
Order By: Relevance
“…The prevalence of I. hexagonus on otters is, however, high in comparison to its prevalence on the domestic dog in the UK (5.6%, n = 3534 [34]). Further, the mean intensity (the total number of parasites of a particular species found in a sample divided by the number of infested hosts [35]) of ticks is higher on otters (7.2 per host) than on hedgehogs (3.8 [36]) despite examination of cadavers in the current study and live hosts in the hedgehog study. This suggests that otters are a noteworthy host for I. hexagonus .…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…The prevalence of I. hexagonus on otters is, however, high in comparison to its prevalence on the domestic dog in the UK (5.6%, n = 3534 [34]). Further, the mean intensity (the total number of parasites of a particular species found in a sample divided by the number of infested hosts [35]) of ticks is higher on otters (7.2 per host) than on hedgehogs (3.8 [36]) despite examination of cadavers in the current study and live hosts in the hedgehog study. This suggests that otters are a noteworthy host for I. hexagonus .…”
Section: Discussioncontrasting
confidence: 59%
“…As far as we are aware, there are no previous records of temperature effects on I. hexagonus and the only long-term study on population dynamics of I. hexagonus indicates little seasonal variation and low-level abundance (on hedgehogs [36]). In general, however; temperature has a key role in driving tick development rates [17], [19] and so affects population dynamics [16], [17].…”
Section: Discussionmentioning
confidence: 91%
“…Hedgehogs can reach up to nine times higher densities in urban areas with parks and garden, than in rural areas, with lowest densities in forests and open grassland fields and agricultural land without cover such as shrubs or dead wood [3032]. Since they are one of the most successful urban adapters, hedgehogs and I. hexagonus could contribute to the spread and persistence of pathogens in a (sub) urban habitat via secondary enzootic cycles, even when the contact between I. hexagonus and humans is low [15, 33]. …”
Section: Introductionmentioning
confidence: 99%
“…On seeing from dorsal side mouthpart observed in anterior parts, palps and hypostome were short, basis capituli distinctly appeared hexagonal shape and length of palp was nearly equal to basis capituli. Several studies have been conducted worldwide which showed high prevalence of this ectoparasite on hedgehog [10,9,19] . This tick had high tendency to infect wild host and immature stages generally infest hedgehogs, gerbils and rodents [3] .…”
Section: Resultsmentioning
confidence: 99%